Baby Boomers and Gen-Z Communication Analysis At PT. Harnawangsa Persada Abadi - Putri, Rahma Nabilla Subarna; Setiawan, Permana; Pahmi, Rizky Abdul; Zakiyyah, Rifdah; Fegiani, Ira; Ratnasari, Risma (SINTESA, 2025)
The focus of this research aims to determine the implementation and communication barriers of Baby Boomers and gen Z at PT Harnawangsa Persada Abadi. The method used in this research is a qualitative method, which is research used to examine the condition of objects in a natural or natural setting with independent variables, namely: communication. The sampling technique used is Purposive Sampling, which is a sampling method carried out by deliberately selecting samples from the population according to the wishes or objectives of the study. Meanwhile, in analyzing the data, researchers used the Miles and Huberman model with data collection methods, data reduction, data presentation, and drawing conclusions. Based on the results of interviews and observations, it is concluded that the Communication Analysis of Baby Boomers & gen Z at PT HPA has implemented the communication dimension, namely the communication climate with six indicators of trust, participatory decision making, honesty, openness in communication, listening in upward communication, and thinking about high performance goals. The informants of this research are commissioner, Sacipa restaurant manager, accounting staff, warehouse admin, and external party ex assistant marketing manager. The results of the research on the communication of Baby Boomers & gen Z are quite good based on the six indicators, if you want to be better, the company is advised to conduct cross-generational training or regular discussion forums